Becoming an internally displaced person in Australia: state border closures during the COVID-19 pandemic and the role of international law on internal displacement. Issue 1 (2nd January 2022) - Ogg, Kate; Simić, Olivera
ABSTRACT: In response to COVID-19, Australian state and territories have, at various times, restricted entry to returning residents. Consequently, many people have been unable to return to their homes, some for significant periods. While there have been discussions of the human rights implications of COVID-19 international travel bans and lockdowns, there has been little consideration of the application of international human rights law to those stranded by internal border closures. In this paper, we contend that these 'stranded' people are internally displaced persons ('IDPs') within the meaning of international law and examine how international law on internal displacement can inform domestic human rights law and processes. In doing so, this paper contributes to scarce scholarship on IDPs in higher-income nation-states and internal displacement associated with pandemics. We argue that while internal border closures were implemented to reduce the spread of COVID-19, the nature of the restrictions and the manner in which they were implemented were a disproportionate interference with rights to freedom of movement, family unity, education, healthcare and culture. Our analysis has lessons for responses to disaster displacement (a phenomenon likely to increase with acceleration of climate change), future pandemics and central themes in international scholarship on IDP protection.